z^3+3iz-1-i=0

Simple and best practice solution for z^3+3iz-1-i=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z^3+3iz-1-i=0 equation:


Simplifying
z3 + 3iz + -1 + -1i = 0

Reorder the terms:
-1 + -1i + 3iz + z3 = 0

Solving
-1 + -1i + 3iz + z3 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + -1i + 3iz + 1 + z3 = 0 + 1

Reorder the terms:
-1 + 1 + -1i + 3iz + z3 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -1i + 3iz + z3 = 0 + 1
-1i + 3iz + z3 = 0 + 1

Combine like terms: 0 + 1 = 1
-1i + 3iz + z3 = 1

Add '-1z3' to each side of the equation.
-1i + 3iz + z3 + -1z3 = 1 + -1z3

Combine like terms: z3 + -1z3 = 0
-1i + 3iz + 0 = 1 + -1z3
-1i + 3iz = 1 + -1z3

Reorder the terms:
-1 + -1i + 3iz + z3 = 1 + -1z3 + -1 + z3

Reorder the terms:
-1 + -1i + 3iz + z3 = 1 + -1 + -1z3 + z3

Combine like terms: 1 + -1 = 0
-1 + -1i + 3iz + z3 = 0 + -1z3 + z3
-1 + -1i + 3iz + z3 = -1z3 + z3

Combine like terms: -1z3 + z3 = 0
-1 + -1i + 3iz + z3 = 0

The solution to this equation could not be determined.

 

See similar equations:

| 14x^2-23ax+3a^2=0 | | z^3+3*i*z=1+i | | 3r^2-16r+2=0 | | 3(x-5)=4(2x+1) | | 6(a+8)=72 | | 5(2)-3(2)+5= | | 22=-11w | | 45-7x=8x+15 | | 4e-5=8.6 | | 69*3= | | 73.9=9c-8 | | 5x-10=x+20 | | 8(x+3)=3(2x+12) | | 3x+4y+2x-y= | | 7-10x=132-45x | | 9/x+1=45/x-7 | | 7(a+2)=21.7 | | 3(y+1)+2(y-3)=-28 | | 10x+5=3(5x+7) | | 45-6x=12x+15 | | 2(4+x)=8+2x | | 13/2.16666666667= | | 2(x-4)=10.6 | | 5-10x=32-17x | | 2.16666666667/13= | | 9x+8y=30 | | 4X=-3*(X+7) | | 274-6x=39x+24 | | 6d+7=2d+7 | | 6x-12-18x-12= | | 5(p+1)-2(p+9)=-1 | | 6x=2x(x+2) | | 5a+20c= | | 6x-13=11+4n | | x^3-2x^2-4x=1 | | 2b-10q= | | -8x+y=22 | | 2x+5/5=3x+1/2+7-x/2 | | 5a+10+15= | | 6x-2-1x-6= | | 3-5(4X-2)=23 | | 6x-2-12x-6= | | 4v^2-1=0 | | 10(x+4)-4(x-2)=3(x-1)+2(x-3) | | 10b+20c=40 | | 125-5x=31x+21 | | 25x+1=-7x+37 | | 3(m+8)-2(m-2)=24 | | x^2+19x-10077696=0 | | 2x-(6x+2)= | | 2f-4=f+3 | | (-9m)*n= | | 11x-18=-9x-17 | | 4(2x-5)=3x+2(x-8) | | 24x-6y=0 | | -4+20=2x | | y^2-50y+225=0 | | 6x+21= | | 4x^2+7+0=0 | | -x=-4.91+.291y | | 9x-5y=12fory | | 8x-2-9x-18= | | 1.8c+9=18 | | 6(3+n)-5(8-n)=0 | | 6x^2+12x-4=0 |